Phase II Study of Personalized Peptide Vaccination with Both a Hepatitis C Virus-Derived Peptide and Peptides from Tumor-Associated Antigens for the Treatment of HCV-Positive Advanced Hepatocellular Carcinoma Patients. (11th October 2015) - Yutani, Shigeru; Ueshima, Kazuomi; Abe, Kazumichi; Ishiguro, Atsushi; Eguchi, Junichi; Matsueda, Satoko; Komatsu, Nobukazu; Shichijo, Shigeki; Yamada, Akira; Itoh, Kyogo; Sasada, Tetsuro; Kudo, Masatoshi; et al.
Abstract : Objective . To evaluate safety and immune responses of personalized peptide vaccination (PPV) for hepatitis C virus- (HCV-) positive advanced hepatocellular carcinoma (HCC). Patients and Methods . Patients diagnosed with HCV-positive advanced HCC were eligible for this study. A maximum of four HLA-matched peptides were selected based on the preexisting IgG responses specific to 32 different peptides, which consisted of a single HCV-derived peptide at core protein positions 35–44 (C-35) and 31 peptides derived from 15 different tumor-associated antigens (TAAs), followed by subcutaneous administration once per week for 8 weeks. Peptide-specific cytotoxic T lymphocyte (CTL) and IgG responses were measured before and after vaccination. Results . Forty-two patients were enrolled. Grade 3 injection site skin reaction was observed in 2 patients, but no other PPV-related severe adverse events were noted. Peptide-specific CTL responses before vaccination were observed in only 3 of 42 patients, but they became detectable in 23 of 36 patients tested after vaccination. Peptide-specific IgG responses were also boosted in 19 of 36 patients. Peptide-specific IgG1 responses to both C-35 and TAA-derived peptides could be potentially prognostic for overall survival. Conclusion . Further clinical study of PPV would be warranted for HCV-positive advanced HCC, based on the safety and strong immune induction.